Information technology of diagnostics of electric motor condition using Volterra models - Григоренко, Светлана Николаевна; Павленко, Сергей Витальевич; Павленко, Виталий Данилович; Фомин, Александр Алексеевич (Eastern-European Journal of Enterprise Technologies, 2014)
The considerable growth of researches on the nonlinear systems based on the Volterra mathematical apparatus of integro-power series was generated by the necessity of using models of real objects of control and operation of enhanced accuracy, totally different from linear models. Moreover, they allow to develop by analogy the created methodological base for solving tasks of identification and diagnosis of dynamic systems at an entirely new level. This research provides the information diagnostic technology of motor operating conditions, which is based on the methods of non-parametric identification of control objects (CO) and building the decision optimal classification rules in the diagnostic feature space. The non-linear dynamic models in the form of the Volterra multidimensional kernels are used as the diagnostic information source, which are identified according to the results of the experimental studies of the control objects “input-output”. The obtained with the help of simulation modeling results of studying the informativeness of the diagnostic features formed on the basis of the Volterra kernels allow to make a conclusion on the effective use of non-parameter dynamic models in the form of the Volterra series for diagnosing electric motors.